1979
DOI: 10.1177/004051757904900604
|View full text |Cite
|
Sign up to set email alerts
|

Physical Chemistry of Dyeing of Cellulosic Fibers with Reactive Dyes

Abstract: The effect of different electrolytes on the sorption of the hydrolyzed form of four different reactive dyes has been investigated. The electrolytes studied were sodium, ammonium, Jithium, and magnesium chlorides, and ammonium sulfate, which differ widely in their ability to increase the sorption of hydrolyzed reactive dyes by cellulose. Their relative efficiencies were in the order: ammonium chloride > ammonium sulfate > sodium chloride > lithium chloride ~ magnesium chloride. The effect of the elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0
1

Year Published

1982
1982
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…At low concentrations, screening effect plays an important role, calcium ions could reduce |] | to a greater extent. However, when the concentration of cation is high, the ability to modify the fibre-water interface plays a decisive role [18]. Since the ability of calcium ion to modify the fibre-water interface is smaller than that of sodium ion, as a result, the rate of the decrease in |] | under the influence of calcium ion became less pronounced with higher concentrations.…”
Section: Zeta Potential Of Silk Fibres Dyed At Alkaline Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…At low concentrations, screening effect plays an important role, calcium ions could reduce |] | to a greater extent. However, when the concentration of cation is high, the ability to modify the fibre-water interface plays a decisive role [18]. Since the ability of calcium ion to modify the fibre-water interface is smaller than that of sodium ion, as a result, the rate of the decrease in |] | under the influence of calcium ion became less pronounced with higher concentrations.…”
Section: Zeta Potential Of Silk Fibres Dyed At Alkaline Conditionmentioning
confidence: 99%
“…With further increase of electrolyte concentration, over 200 ppm, the influence of dye exhaustion and fixation caused by calcium ions become less, while in the case of sodium ions, the dye exhaustion and fixation increase in a linear manner. When the concentration of electrolytes is high, the ability of the electrolyte to modify the fibre-water interface [18] and to disrupt the water structure of hydrated water around the hydrophobic parts of dye molecules [23] will play a decisive role. It can therefore be postulated that because the abilities of calcium ions to modify fibre-water interface and to disrupt the structure of hydrated water is smaller than that of sodium ions, their promoting effect on exhaustion and fixation becomes smaller.…”
Section: Dyeing Of Silk At Different Conditionsmentioning
confidence: 99%
“…Madan and Shrivastava [7] and Sivaraja Iyer and Subramanian [ 13] reported that, in addition to the suppression of surface potentials that help the dye adsorption process on cellulose, cations influence the dye adsorption by disrupting the structure of water bound to the surface of cellulose. In this report, we first indicate that adsorption of direct dye on cellulose in the presence of different kinds of counterions increases in the order Cs+ > K+ > Na+.…”
mentioning
confidence: 99%
“…In addition to the fact mentioned above for counterions on dye adsorption, the cation for electrolyte may influence the dye adsorption by the well known effect of electrolytes suppressing surface potential, which helps the dye adsorption process [7,13]. Madan [7] and Sivaraja Iyer [!3] also reported that cations for electrolytes influenced the dye adsorption by disrupting the structure of water bound to the surface of cellulose.…”
mentioning
confidence: 99%
See 1 more Smart Citation